Kepatuhan Konsumsi Tablet Fe dan Pencegahan Anemia pada Remaja Putri di Indonesia: Meta-Analisis - Simbolon, Demsa; Anggraini, Hera; Sari, Ayu Prapita (Universitas Islam Negeri Walisongo Semarang, 2023)
The study aimed to determine the estimated combined effect of Fe tablet consumption on the incidence of anemia in adolescent girls. The research design used was Meta-analysis. The literature was searching from Pub-Med and Google Scholar articles. The article criteria were: (1) articles which published in 2017-2022; (2) articles with research conducted in Indonesia; (3) articles which can be downloaded full-tex; (4) articles with case control and cross-sectional studies; (5) articles with available Odd Ratio data. The searching keywords used were